Reduction of motion artifacts in carotid MRI using free-induction decay navigators - Dyverfeldt, Petter; Deshpande, Vibhas S.; Kober, Tobias; Krueger, Gunnar; Saloner, David (Journal of magnetic resonance imaging, 2014)
Purpose To develop a framework for prospective free‐induction decay (FID)‐based navigator gating for suppression of motion artifacts in carotid magnetic resonance imaging (MRI) and to assess its capability in vivo. Materials and Methods An FID‐navigator, comprising a spatially selective low flip‐angle sinc‐pulse followed by an analog‐to‐digital converter (ADC) readout, was added to a conventional turbo spin‐echo (TSE) sequence. Real‐time navigator processing delivered accept/reject‐and‐reacquire decisions to the sequence. In this Institutional Review Board (IRB)‐approved study, seven volunteers were scanned with a 2D T2‐weighted TSE sequence. A reference scan with volunteers instructed to minimize motion as well as nongated and gated scans with volunteers instructed to perform different motion tasks were performed in each subject. Multiple image quality measures were employed to quantify the effect of gating. Results There was no significant difference in lumen‐to‐wall sharpness (2.3 ± 0.3 vs. 2.3 ± 0.4), contrast‐to‐noise ratio (CNR) (9.0 ± 2.0 vs. 8.5 ± 2.0), or image quality score (3.1 ± 0.9 vs. 2.6 ± 1.2) between the reference and gated images. For images acquired during motion, all image quality measures were higher (P < 0.05) in the gated compared to nongated images (sharpness: 2.3 ± 0.4 vs. 1.8 ± 0.5, CNR: 8.5 ± 2.0 vs. 7.2 ± 2.0, score: 2.6 ± 1.2 vs. 1.8 ± 1.0). Conclusion Artifacts caused by the employed motion tasks deteriorated image quality in the nongated scans. These artifacts were alleviated with the proposed FID‐navigator. J. Magn. Reson. Imaging 2014;40:214–220. © 2013 Wiley Periodicals, Inc.